(untitled) (Research Nepal Journal of Development Studies, 2019)
Foreign employment has provided alternative opportunities for livelihood and contributed for a remittance based economy in Nepal at present. In the context of Nepal, the present study has been carried out with the overall objective to explore the roles of remittances in terms of both monetary and social capital gained from foreign employment in entrepreneurship development, particularly agribusiness enterprises owned by the returnee migrant workers in Nepal. In terms of framework, the study has followed the migration in optimistic perspective. The study has shown that the economic status of the majority of respondents has improved since beginning their agribusiness enterprises. In addition to economic status, the social status of the respondents has also seen improvements through operating their agribusiness. Remittances gained from foreign employment has been an unavoidable factor for entrepreneurship development in the country of origin. But, the important thing is; whether the remittances have been used in the productive sectors, particularly in entrepreneurship development or not. Capital investment, employment creation, research and innovation are seen the opportunities of agribusiness which can lead to the sustainable livelihood of returnee migrant workers. In turn, policy reforms and strategic project interventions from concerned authorities are critically important for the entrepreneurship and productive use of the remittance.